Bang Bua Thong Melayu Dialect - a Lexicon Study - Umar, Umaiyah Haji (Journal of Language and Culture, 2014)
In and around Bangkok, Thailand there are various minority ethnic groups living in small communities who still retain their cultural identities. This study is on the Malay language used by Malay Community of Bang Bua Thong in Nonthaburi Province, immediately North of Bangkok. They are descendants of Kedah and Pattani prisoners who were forcibly brought for resettlement some 200 years ago. The focus will be on Malay words used in everyday life, in order to investigate how the formation of words can affect their meanings as well as to identify the borrowing process which affects of the words. Field interviews were carried out in the area after carefully selecting respondents. The study, which covers lexicon and touches on phonology, shows that the language has evolved more in terms of lexicon whilst retaining its phonology. <span style="font-size: 10.0pt; font-family: ’Tahoma’,’sans-serif’; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">An interesting extension of this study is to trace the origins of the people through the language’s phonological roots.